Morphology Transformation of Supramolecular Structures in Aqueous Mixtures of Two Oppositely Charged Amphiphiles - Liang, Wenlang (Langmuir : the ACS journal of surfaces and colloids, 2019)
The co-assembly of oppositely charged amphiphiles provides a fascinating approach for forming complex supramolecular structures, which are interesting from both fundamental and technological viewpoints. Here, we report a stepwise morphology transformation of co-assembled supramolecular structures in the aqueous mixture of lithocholic acid (LCA) and cetyltrimethylammonium bromide (CTAB) at mixed molar ratios of 1:1 and 2:1. The co-assembly of LCA and CTAB initially forms multilamellar vesicles followed by the spontaneous growth of membrane tubes from the vesicles. The vesicle-to-tube transition is accompanied by a fluidic-to-crystalline phase transition. After being aged, the membrane tubes twist into left-handed helices, which then intertwine into left-handed double helices and multihelix bundles. The single handedness of these supramolecular structures is a reflection of the amplification of the chirality of LCA. An understanding of the co-assembly mechanism and pathway is a key step toward producing supramolecular structures with distinguished morphologies